Optimization of Human Resource Planning to Support the Free Nutritional Meal Program in Order to Achieve a Strong National Defense - Ariska, Hendra Tri; Faisol, Achmad; Nugroho, Panji Agung (Journal of Industrial Engineering & Management Research, 2025)
The free nutritious meal program initiated by the Prabowo-Gibran administration in the 2024 election aims to improve the nutrition and health of children, especially in remote areas, by providing free lunch and milk in schools and pesantren. This program targets more than 82 million people and requires an annual budget of Rp 450 trillion. While it has gained support due to its potential benefits for children’s health and performance, it also faces criticism as a consumptive policy. Countries such as the United States and Finland have successfully implemented similar programs with positive impacts on health and the economy. This research aims to analyze the role of the Indonesian Navy (TNI AL) in human resource (HR) planning to support the free nutritious meal program. The research method used in this study is qualitative. The findings indicate that the success of the free nutritious meal program in supporting national defense depends on the role of the TNI AL in addressing three key factors: HR competency, logistics management, and oversight. The TNI AL can enhance HR competency through structured planning and competency-based training, improve logistics efficiency by forming cross-sectoral coordination teams, and ensure optimal oversight with trained monitoring teams and technology-based monitoring systems.